Decision Support System for Property Insurance Selection Using Simple Additive Weighting (SAW) Method - Anggraini Kusumaningrum; Astika Ayuningtyas; Leonardo Tampubolon; Anton Honggowibowo; Haruno Sajati; Mardiana Irawaty (University of Technology Yogyakarta, 2021)
Every human being cannot predict what events will happen to him, whether natural disasters or non-natural disasters that can befall his property assets. Property insurance is a type of protection for property assets such as houses, apartments, and offices. The goal is to anticipate financial losses due to unexpected events that befall your property. Data such as Risk-Based Capital (RBC) is needed in choosing a property insurance company, the amount of premium, insurance coverage, and the premium period as a material consideration in making decisions. In implementing the Property Insurance Selection Decision Support System Application using the Simple Additive Weighting (SAW) method, the user determines the main priority weights from the predetermined criteria, from the results of determining the priority weights, a recommendation for property insurance companies is obtained which is desired by the property owner from the calculation results, it can be concluded that the average calculation speed of the application of 30 experimental sample data is 1264 ms or 1.264s